A CLOSER LOOK AT CHALLENGES IN THE EFL ONLINE TEACHING DURING THE COVID-19 PANDEMIC - Baiq Jihan Olvy Wanasatya; Muhammad Amin; Lalu Thohir (Program Studi Pendidikan Bahasa Inggris, 2022)
Corona Virus spreading in 2020 caused all schools were temporarily closed and the learning process must be conducted online. Teachers had to adjust their learning method to the situation. It was new encounter for them to apply online learning which led to various challenges. The present study aimed to figure out how English teachers apply online teaching during the pandemic, what challenges they faced, and what strategies they used to overcome those challenges and turn it into opportunities so as they could succeed in online learning. This is a qualitative descriptive study which involved four English teachers in a state junior high school in Mataram. In obtaining the data needed, an open-ended questionnaire and semi-structured interview were applied. The obtained data were then analyzed through data reduction, data display, and conclusion drawing. The findings showed that English teachers conducted online teaching via Zoom, Google Classroom, WhatsApp, and Google Form. The teachers faced some challenges such as unavailable digital devices, unstable internet connection, limited internet data plan, teachers and student’s inability to use technology, and the lack of student’s motivation and the teachers applied some strategies to overcome those challenges. Further, some opportunities were provided for the teachers such as online teaching which could enhance teachers' digital literacy and develop their competency in using technology.